2009
DOI: 10.1109/tevc.2009.2025455
|View full text |Cite
|
Sign up to set email alerts
|

Effective Linkage Learning Using Low-Order Statistics and Clustering

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 24 publications
(69 reference statements)
2
45
0
Order By: Relevance
“…For instances with 2-4 objectives, MOEA/D exhibits the best performance, however it is closely followed by However for more than 9 objectives, random search out-performs the other algorithms. Also, when compared with RM-MEDA, both MACE and MACE-gD perform significantly better for all instances with 2-10 objectives, a fact that supports the theory presented in [36] that EDAs using low order statistics with some form of clustering have potential. Of course, clustering is not used in these versions of the MACE algorithm; this is the subject of future research.…”
Section: Experiments Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…For instances with 2-4 objectives, MOEA/D exhibits the best performance, however it is closely followed by However for more than 9 objectives, random search out-performs the other algorithms. Also, when compared with RM-MEDA, both MACE and MACE-gD perform significantly better for all instances with 2-10 objectives, a fact that supports the theory presented in [36] that EDAs using low order statistics with some form of clustering have potential. Of course, clustering is not used in these versions of the MACE algorithm; this is the subject of future research.…”
Section: Experiments Resultssupporting
confidence: 81%
“…This is fortunate since the CE method is based on sound theoretical principles which can facilitate further analysis of this method. Also, the hypothesis presented in [36], that EDAs based on low order statistics and clustering can be used as an alternative to complex probabilistic models, seems to be supported by the obtained results in Section VII-C. However, as no clustering method is employed in MACE-gD, this does not constitute solid proof but it is certainly a good indication.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Estimation of Distribution Algorithms (EDAs) (Larrañaga and Lozano 2002) that employ this technique are (Emmendorfer and Pozo 2009;Pelikan and Goldberg 2000;Tsuji et al 2006;Bosman and Thierens 2002).…”
Section: Clustering In Single Objective Optimizationmentioning
confidence: 99%
“…Thus conveying local minimum instead of global minimum. In his work, Emmendorfer [18] showed that a mixture of Gaussians, as a multimodal distribution, is a good alternative to model non-convex search spaces.…”
Section: Pbil and Clusteringmentioning
confidence: 99%